Effect of neonatal neuronal intensive care unit on neonatal encephalopathy - Lin, Lu; Liu, Weiqin; Mu, Jing; Zhan, Enmei; Wei, Hong; Hong, Siqi; Hua, Ziyu (PloS one, 2021)
Prophylaxis of brain injury in newborns has been a main concern since the first neonatal neuronal intensive care unit (NNICU) was established in the world in 2008. The aim of this study was to outline and evaluate the unit’s development by analyzing the demographics of the patients, the services delivered, the short-term outcomes before and after the establishment of NNICU. During the two investigation periods, 384 newborns were diagnosed or suspected as “neonatal encephalopathy”, among which 185 patients admitted to NNICU between 2011.03.01 and 2012.09.30 before the establishment of NNICU were enrolled in the pre-NNICU group, another 199 neonates hospitalized during 2018.03.01 to 2019.09.30 were included in the post-NNICU group. Patients in the post-NNICU group were more likely to have seizures ( P = 0.001), incomplete or absent primitive reflexes ( P = 0.002), therapeutic hypothermia ( P <0.001) and liquid control ( P <0.001) in acute phase. Meanwhile, amplitude-integrated electro encephalogram (aEEG) monitoring ( P <0.001) and cranial ultrasound ( P <0.001) were more often used in NNICU. Both of the follow-up rate in brain MRI and the assessment of neurodevelopment at 3 months were higher in the post-NNICU group ( P <0.001). In conclusion, the NNICU focused on the neonatal neurocritical care for the babies susceptible to NE with the guidance of evidence-based medicine, the establishment of NNICU is gradually improving and standardizing the neuroprotective therapy and clinical follow-up to improve neurodevelopmental prognosis of the NE patients in CHCMU.